Stress and Occupational Coping among Brazilian Nurses in Critical Care Units during the COVID-19 Pandemic - Meneguin, Silmara [UNESP] (2024)
Objective: To investigate the effects of sociodemographic and working condition variables, as well as the coping strategies used by nurses, on their occupational stress during the COVID-19 pandemic. Methods: A cross-sectional study was conducted with 104 nurses who worked in intensive and emergency care at a public hospital in the state of São Paulo, Brazil. Data collection was performed in person and online using a questionnaire assessing sociodemographic and occupational characteristics, the Nursing Stress Inventory, and the Occupational Coping Scale. Results: The participants had a high level of stress (median = 132), especially in the ‘interpersonal relations’ domain (median = 63), and made little use of occupational coping strategies (median = 87). Income (p = 0.027), work shift (p = 0.028), being on leave from work (p = 0.020), number of hospitals with employment ties (p = 0.001), and relationship with management were independently associated with the levels of stress among the nurses. Conclusion: In the present study, the high levels of stress among nurses were influenced by financial and work-related factors as well as interpersonal relationships. No significant association was found between stress among the nurses and the use of occupational coping strategies.